Halal Assessment Model Design in Bakery Industry - Putri, Alyani Rahma; Putri, Nilda Tri; Hasan, Alizar; Arief, Ikhwan; Abdul Talib, Hayati Habibah (Indonesian Journal of Halal Research, 2021)
Bakery product is a product with huge business opportunities in the domestic and international halal food market. Bakery companies demand to keep consumers' trust in their bakery products. This study aims to design the halal assessment model required to determine the critical point in the bakery-making business process. This assessment tool is intended to understand, acknowledge, and determine the critical point of the bakery production process from the halal degree and is reviewed from all aspects, such as the materials’ content, as well as the material acquisition and processing method based on 18 criteria of Good Manufacturing Practices (GMP) principles. The halal assessment model designed in this research used the Quality Function Deployment (QFD) approach, which was integrated into the company's business process. The halal critical bakery (HCB) was grouped based on Supply Chain Operations Reference (SCOR) model. Matrix 1 integrated GMP and business process (BP), and matrix 2 integrated GMP and HCB. The results of the design model implementation based on the standards set by the Halal Auditor of Institute for the Study of Food, Drugs, and Cosmetics Indonesian Ulema Council (LPPOM MUI) found that the company met the standard matrix component one by 47%. In comparison, matrix component 2 was only able to meet the Auditor standards by 34%, and the matrix component 3 standards were able to be fulfilled by the company by 75%. The fulfillment value of each matrix is influenced by the negative gap that occurs; the negative gap occurs because of the standard criteria in the technical matrix that are not accomplished. This halal assessment model design is expected to help the company evaluate and control critical points in the business processes.